Scaling coefficient for three-dimensional grain coalescence of ZnO on Si(111) - Ruth, Marcel; Meier, Cedrik (Physical Review B)

Carrier localization in ZnO quantum wires - Kröger, Philipp; Ruth, Marcel; Weber, Nils; Meier, Cedrik (Applied Physics Letters)

Enhanced photoluminescence of colloidal nanocrystals embedded in epitaxially grown semiconductor microstructures - Kampmeier, J.; Rashad, M.; Woggon, U.; Ruth, M.; Meier, Cedrik; Schikora, D.; Lischka, K.; Pawlis, A. (Physical Review B)

Quasar 3.0 - A Situational Approach to Software Engineering - Kremer, Marion; Engels, Gregor; Hofmann, Alexander; Hohwiller, Jörg; E. Nandico, Oliver; Nötzold, Thomas; Prott, Karl; Schlegel, Diethelm; Seidl, Andreas; Wolf, Thomas

Model-Based Testing: Achievements and Future Challenges - Mlynarski, Michael; Güldali, Baris; Weißleder, Stephan; Engels, Gregor (Advances in Computers)
Software systems are part of our everyday life and they become more complex day by day. The ever-growing complexity of software and high quality requirements pose tough challenges to quality assurance. The quality of a software system can be measured by software testing. However, if manually done, testing is a time-consuming and error-prone task. Especially test case design and test execution are the most cost-intensive activities in testing. In the previous 20 years, many automation tools have been introduced for automating test execution by using test scripts. However, the effort for creating and maintaining test scripts remains. Model-based testing (MBT) aims at improving this part by systematizing and automating the test case design. Thereby, test cases or automatable test scripts can be generated systematically from test models. MBT is already known for several years, but it currently gains a great momentum due to advanced tool support and innovative methodological approaches. This chapter aims at giving an overview of MBT and summarizes recent achievements in MBT. Experiences with using the MBT approach are illustrated by reporting on some success stories. Finally, open issues and future research challenges are discussed.

Automatische Kompatibilitätsprüfung Framework-basierter Anwendungen - Christ, Fabian
Software-Architekturen betrieblicher Informationssysteme bestehen aus Architekturbausteinen wie Frameworks, Komponenten und Bibliotheken. Die Entwicklung dieser Architekturen unter Einbeziehung wiederverwendbarer Architekturbausteine ist eine Voraussetzung einer industriell organisierten Software-Entwicklung. Für eine effiziente Trennung der Zuständigkeiten werden dabei häufig Architekturbausteine von Drittanbietern wiederverwendet.Frameworks als erweiterbare Architekturbausteine bieten besondere Vorteile. Sie erlauben sowohl die Wiederverwendung der Funktionalität als auch der durch das Framework vorgegebenen Software-Architektur. Beispiele sind Frameworks für Benutzungsoberflächen oder für die Anbindung von Datenbanken. Durch Implementierung anwendungsspezifischer Erweiterungen wird ein Framework für den konkreten Anwendungsfall angepasst. Eine Anwendung, deren Software-Architektur ein Framework einsetzt, benutzt das Framework über dessen Erweiterungspunkte.Im Laufe der Evolution einer solchen Anwendung entsteht häufig die Situation, dass das Framework durch eine neuere Version aktualisiert werden soll. Die Aktualisierung enthält das Risiko, dass Inkompatibilitäten zwischen bestehender Anwendung und neuer Framework-Version auftreten, die wiederum zu aufwendigen Anpassungen führen. Daher müssen mögliche Inkompatibilitäten vor der Aktualisierung erkannt und bewertet werden. Nach aktuellem Stand der Technik ist dies nicht möglich, so dass es in der industriellen Praxis zu unvorhergesehenen Problemen verbunden mit hohen Kosten kommt.Wir stellen ein Verfahren zur automatischen Kompatibilitätsanalyse Framework-basierter Anwendungen vor, mit dem das beschriebene Problem gelöst wird. Durch eine Kombination aus Codeanalyse und neuartiger Framework-Beschreibung lassen sich mögliche Inkompatibilitäten vor Durchführung der Aktualisierung automatisch berechnen. Eine prototypische Implementierung des Verfahrens im Werkzeug »Companian« demonstriert die praktische Einsetzbarkeit unseres Verfahrens.Für die Definition der benötigten Framework-Beschreibungssprache mittels Meta-Modellierung setzen wir die neuartige Modellierungstechnik der parametrisierten Meta-Modelle ein. Die Technik unterstützt unseren Ansatz einer anforderungsbasierten Wiederverwendung von Sprachen. Mit diesem Ansatz können bestehende Sprachen für Teilaspekte neu definierter Sprachen wiederverwendet werden. Unser pragmatischer Ansatz stellt dabei sicher, dass hierbei nur die Sprachen benutzt werden können, die syntaktisch und semantisch den geforderten Sprachen entsprechen.

Towards Rich Change Management for Business Process Models - Gerth, Christian; Luckey, Markus (Proceedings of the Workshop on Comparison and Versioning of Software Models (CVSM'12))

A UML-based Rich Service Description Language for Automatic Service Discovery of Heterogeneous Service Partners - Huma , Zille; Gerth , Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the Forum at the CAiSE'12 Conference on Advanced Information Systems Engineering)

Modeling with Adapt Cases - Luckey , Markus; Mutz, Felix (Repository for Model-Driven Development (ReMoDD))

Ein Ansatz zur dynamischen Qualitätsmessung, -bewertung und Anpassung von Software Engineering Methoden - Geisen , Silke; Luckey , Markus; Engels, Gregor (Proceedings of 19. GI-WIVM Workshop: Qualitätsmanagement und Vorgehensmodelle)

Towards a Framework for the Integration of Modeling Languages - Arifulina, Svetlana (Proceedings of the Doctoral Symposium of the 5th International Conference on Software Language Engineering 2012, Dresden, Germany (SLE (Doctoral Symposium)))

Entwicklung eines Softwarewerkzeugs für die modellgetriebene Migration betrieblicher Informationssysteme - Güldali , Baris; Sauer, Stefan; Löhr, Perdita (Proceedings of the Workshop Modellbasierte und Modellgetriebene Softwaremodernisierung (MMSM 2012))

Assessing composition in modeling approaches - Mussbacher , Gunter; Alam , Omar; Alhaj , Mohammed; Ali , Shaukat; Amálio , Nuno; Barn , Balbir; Bræk , Rolv; Clark , Tony; Combemale , Benoit; Cysneiros , Luiz Marcio; Fatima , Urooj; France , Robert; et al. (Proceedings of the Workshop about Comparing Modeling Approaches 2012 (@MODELS 2012))

Multi-Staged Quality Assurance for Self-Adaptive Systems - Luckey , Markus; Thanos , Christian; Gerth, Christian; Engels, Gregor (Proceedings of 1st International Workshop on EVALUATION for SELF-ADAPTIVE and SELF-ORGANIZING SYSTEMS at SASO'12)

Ein Ansatz zur Anpassung von Software Engineering Methoden im laufenden Projekt - Geisen, Silke (Proceedings of Software Engineering 2012 (SE 2012) - Doktorandensymposium)

Mathematikinteresse im 1. Studiensemester - Liebendörfer, Michael; Hochmuth, Reinhard (Beiträge zum Mathematikunterricht 2012 : Vorträge auf der 46. Tagung für Didaktik der Mathematik)

Training of student teaching assistants and e-learning via math-bridge – Two projects at the German Centre for Higher Mathematics Education - Biehler, Rolf; Hoppenbrock, Axel; Klemm, Juliane; Liebendörfer, Michael; Wassong, Thomas (CETL-MSOR Conference 2011)

The Cox ring of the space of complete rank two collineations - Hausen, Jürgen; Liebendörfer, Michael (Mathematische Nachrichten)
We consider the space of complete rank two collineations. Starting from its description as a limit of GIT-quotients of a Grassmanian G(2, n) by a certain {\}documentclass\{article\}{\}usepackage\{amssymb\}{\}begin\{document\}{\}pagestyle\{empty\}\${\}mathbb \{C\}{\textasciicircum}*\${\}end\{document\}-action, we determine the Cox ring by means of toric ambient modifications.

Vorstellung des Modellprojekts InLab - Beutner, Marc; Kremer, H.-Hugo; Zoyke, A (Individuelle Förderung und berufliche Orientierung im berufsschulischen Übergangssystem. Ergebnisse aus dem Forschungs- und Entwicklungsprojekt InLab)

Vorstellung von vier Instrumenten zur Individuellen Förderung - Beutner, Marc; Frehe, Petra; Gebbe, M; Gockel, C; Kremer, H.-Hugo; Zoyke, A (Individuelle Förderung und berufliche Orientierung im berufsschulischen Übergangssystem. Ergebnisse aus dem Forschungs- und Entwicklungsprojekt InLab)

Victorian Values in Nineteenth- and Twenty-First-Century Advertising and Consumer Practices - Strauß, Sara (anglistik & englischunterricht)

Facets of Children’s Fears in Twentieth- and Twenty-First-Century Stream-of-Consciousness Fiction - Strauß, Sara (Who’s afraid of...? Facets of Fear in Anglophone Literature and Film)

Constructions of ‘Otherness’ in Frances Hodgson Burnett’s The Secret Garden - Strauß, Sara (A Hundred Years of The Secret Garden – Frances Hodgson Burnett’s Children’s Classic Revisited)

The Persistence of Modernism in Light (Critical Engagements: A Journal of Criticism and Theory: Special Section: Eva Figes)

Der Zauber Magischer Welten - Flotmann, Christina
Interview 11 Oct. 2012

Frequency tuning of piezoelectric energy harvesters by magnetic force - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Smart Materials and Structures)
A piezoelectric energy harvester is an electromechanical device that converts ambient mechanical vibration into electric power. Most existing vibration energy harvesting devices operate effectively at a single frequency only, dictated by the design of the device. This frequency must match the frequency of the host structure vibration. However, real world structural vibrations rarely have a specific constant frequency. Therefore, piezoelectric harvesters that generate usable power across a range of exciting frequencies are required to make this technology commercially viable. Currently known harvester tuning techniques have many limitations, in particular they miss the ability to work during harvester operation and most often cannot perform a precise tuning. This paper describes the design and testing of a vibration energy harvester with tunable resonance frequency, wherein the tuning is accomplished by changing the attraction force between two permanent magnets by adjusting the distance between the magnets. This tuning technique allows the natural frequency to be manipulated before and during operation of the harvester. Furthermore the paper presents a physical description of the frequency tuning effect. The experimental results achieved with a piezoelectric bimorph fit the calculated results very well. The calculation and experimental results show that using this tuning technique the natural frequency of the harvester can be varied efficiently within a wide range: in the test setup, the natural frequency of the piezoelectric bimorph could be increased by more than 70%.

Analytical determination of characteristic frequencies and equivalent circuit parameters of a piezoelectric bimorph - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Journal of Intelligent Material Systems and Structures)
Piezoelectric structures are nowadays used in many different applications. A better understanding of the influence of material properties and geometrical design on the performance of these structures helps to develop piezoelectric structures specifically designed for their application. Different equivalent circuits have been introduced in the literature to investigate the behaviour of piezoelectric transducers. The model parameters are usually determined from measurements covering the characteristic frequencies of the piezoelectric transducer. This article introduces an analytical technique for calculating the mechanical and electrical equivalent system parameters and characteristic frequencies based on material properties and geometry for a cantilever bimorph structure. The model is validated by measurements using a cantilever bimorph and fits the experimental results better than previous models. The model gives a full set of piezoelectric transducer parameters and is therefore well suited for further theoretical investigations of piezoelectric transducers for different applications. The results also show that even small manufacturing tolerances have a considerable effect on the system parameters and characteristic frequencies. This might lead to intolerable deviations, especially in dynamic applications and should be avoided by careful design and production.

Non-perturbing cavitation detection / monitoring in sonochemical reactors - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Maeda, Takafumi; Morita, Takeshi (Ultrasonics Symposium (IUS), 2012 IEEE International)
To optimize the ultrasound irradiation for cavitation based ultrasound applications like sonochemistry or ultrasound cleaning, the correlation between cavitation intensity and the resulting effect on the process is of interest. Furthermore, changing conditions like temperature and pressure result in varying acoustic properties of the liquid. That might necessitate an adaption of the ultrasound irradiation. To detect such changes during operation, process monitoring is desired. Labor intensive processes, that might be carried out for several hours, also require process monitoring to increase their reliability by detection of changes or malfunctions during operation. In some applications cavitation detection and monitoring can be achieved by the application of sensors in the sound field. Though the application of sensors is possible, this necessitates modifications on the system and the sensor might disturb the sound field. In other applications harsh, process conditions prohibit the application of sensors in the sound field. Therefore alternative techniques for cavitation detection and monitoring are desired. The applicability of an external microphone and a self-sensing ultrasound transducer for cavitation detection were experimentally investigated. Both methods were found to be suitable and easily applicable.
Keywords: cavitation; chemical reactors; microphones; process monitoring; reliability; ultrasonic applications; ultrasonic waves; acoustic properties; cavitation based ultrasound applications; cavitation intensity; change detection reliability; external microphone; malfunction detection reliability; nonperturbing cavitation detection; nonperturbing cavitation monitoring; process monitoring; self-sensing ultrasound transducer; sonochemical reactors; sonochemistry; ultrasound cleaning; ultrasound irradiation; Acoustics; Liquids; Monitoring; Sensors; Sonar equipment; Transducers; Ultrasonic imaging

An efficient simulation technique for high-frequency piezoelectric inertia motors - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Ultrasonics Symposium (IUS), 2012 IEEE International)
Piezoelectric inertia motors use the inertia of a body to drive it by means of a friction contact in a series of small steps. These motors can operate in ``stick-slip'' or ``slip-slip'' mode, with the fundamental frequency of the driving signal ranging from several Hertz to more than 100 kHz. To predict the motor characteristics, a Coulomb friction model is sufficient in many cases, but numerical simulation requires microscopic time steps. This contribution proposes a much faster simulation technique using one evaluation per period of the excitation signal. The proposed technique produces results very close to those of timestep simulation for ultrasonics inertia motors and allows direct determination of the steady-state velocity of an inertia motor from the motion profile of the driving part. Thus it is a useful simulation technique which can be applied in both analysis and design of inertia motors, especially for parameter studies and optimisation.
Keywords: friction; ultrasonic motors; Coulomb friction model; efficient simulation technique; friction contact; high-frequency piezoelectric inertia motor; motor characteristics prediction; numerical simulation; slip-slip mode; stick-slip mode; time-step simulation; ultrasonic inertia motor; Acceleration; Acoustics; Actuators; Computational modeling; Friction; Numerical models; Steady-state

Synthesis of piezoelectric materials by ultrasonic assisted hydrothermal method - Isobe, Gaku; Ageba, Ryo; Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (AIP Conference Proceedings)
Hydrothermal method enables to synthesize high quality piezoelectric materials. To shorten the reaction time and to get higher quality materials, we propose an ultrasonic irradiation to the solution during the hydrothermal method. We named it ultrasonic assisted hydrothermal method (UAHTM). We have synthesized lead-free piezoelectric material and PZT thin film and the effect of UAHTM have been confirmed. In this study, we tried to improve UAHTM. First, to generate powerful and stable ultrasonic irradiation at high temperature on UAHTM, we developed a new transducer using LiNbO3 single crystal. Second, to prevent contamination to the materials, A Teflon cover on the tip of transducer was attached.
Keywords: contamination; lead compounds; piezoelectric materials; piezoelectric thin films; piezoelectric transducers; ultrasonic effects

Probabilistic Planning for Predictive Condition Monitoring and Adaptation Within the Self-Optimizing Energy Management of an Autonomous Railway Vehicle - Klöpper, Benjamin; Sondermann-Wölke, Christoph; Romaus, Christoph (Journal of Robotics and Mechatronics)
Self-optimizing mechatronic systems are a new class of technical systems. On the one hand, new challenges regarding dependability arise from their additional complexity and adaptivity. On the other hand, their abilities enable new concepts and methods to improve the dependability of mechatronic systems. This paper introduces a multi-level dependability concept for selfoptimizing mechatronic systems and shows how probabilistic planning can be used to improve the availability and reliability of systems in the operating phase. The general idea to improve the availability of autonomous systems by applying probabilistic planning methods to avoid energy shortages is exemplified on the example of an innovative railway vehicle.
Keywords: self-optimizing systems; dependability; probabilistic planning; energy management

Benteler Vehicle Dynamics -- Fahrdynamikentwicklung basierend auf einer neuen Auslegungstheorie - Kohl, Sergej; Sextro, Walter; Zuber, Armin (8. Tag des Fahrwerks, Aachen, 2012)

Piezoelectric applications of hydrothermal lead-free (K0.48Na0.52)NbO3 ceramics - Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics Symposium (IUS), 2012 IEEE International)
A hydrothermal method utilizes a crystallization process in the solution so that the pure and high-quality powders can be realized. Sintering from the hydrothermal KNbO3 and NaNbO3 powders, a high-dense lead-free piezoelectric (K,Na)NbO3 ceramics could be obtained (density: 98.8%). Concerning about the g33 constant, high value as large as commercial PZT ceramics was measured. Therefore, the hydrothermal (K,Na)NbO3 ceramics is usable for the sensors and the energy harvesting devices. To demonstrate the (K,Na)NbO3 ceramics, a hydrophone sensor was fabricated and evaluated.
Keywords: crystallisation; hydrophones; piezoceramics; potassium compounds; powder technology; powders; sensors; sintering; sodium compounds; (K0.48Na0.52)NbO3; KNbO3 powder; NaNbO3 powder; crystallization; energy harvesting devices; g33 constant; hydrophone sensor; hydrothermal lead-free (K0.48Na0.52)NbO3 ceramics; hydrothermal method; piezoelectric applications; sintering; Materials; Transducers

Piezoelectric Properties of Li-Doped (K0.48Na0.52)NbO3 Ceramics Synthesized Using Hydrothermally-Derived KNbO3 and NaNbO3 Fine Powders - Maeda, Takafumi; Hemsel, Tobias; Morita, Takeshi (Japanese Journal of Applied Physics)
[$Li_x(Na_0.52K_0.48)_1-x]NbO_3 (0 ≤ x ≤ 0.091)$ ceramics were synthesized using hydrothermal powders and the lithium doping content was controlled to optimize their piezoelectric properties. The raw KNbO$_3$ and NaNbO$_3$ powders were obtained separately by a hydrothermal method and LiNbO$_3$ powders were prepared by milling a commercial LiNbO$_3$ single crystal. These powders were mixed with ethanol at a molar ratio LiNbO$_3$: ($Na_0.52K_0.48$)NbO$_3 = x : 1-x$. The synthesized powders were sintered at 1060--1120 $\,^{°}$C for 2 h. We succeeded in obtaining highly dense [$Li_x(Na_0.52K_0.48)_1-x]NbO_3$ ceramics using hydrothermal powder. The X-ray diffraction patterns revealed that the crystal phase changed from orthorhombic to tetragonal at around x = 0.06. At this morphotropic phase boundary (MPB), the c/a ratio changed from 1.016 to 1.024 and the highest piezoelectric constant was obtained with the chemical component of [$Li_x(Na_0.52K_0.48)_1-x]NbO_3$. The obtained piezoelectric properties were as follows: $k_33 = 0.51, ε 33^T/ ε _0 = 836$ , $c_33^E = 46$ GPa, $d_33 = 203$ pC/N, and $T_c = 482 $\,^{°}$C$.

Conceptual Design of Advanced Condition Monitoring for a Self-Optimizing System based on its Principle Solution - Sondermann-Wölke , Christoph; Meyer, Tobias; Dorociak, Rafal; Gausemeier, Jürgen; Sextro, Walter (Proceedings of the 11th International Probabilistic Safety Assessment and Management Conference (PSAM11) and The Annual European Safety and Reliability Conference (ESREL2012))
The rapid development of communication and information technology opens up fascinating perspectives, which go far beyond the state of the art in mechatronics: mechatronic systems with inherent partial intelligence. These so called self-optimizing systems adapt their objectives and behavior autonomously and flexibly to changing operating conditions. On the one hand, securing the dependability of such systems is challenging due to their complexity and non-deterministic behavior. On the other hand, self-optimization can be used to increase the dependability of the system during its operation. However, it has to be ensured, that the self-optimization works dependable itself. To cope with these challenges, the multi-level dependability concept was developed. It enables predictive condition monitoring, influences the objectives of the system and determines suitable means to improve the system's dependability during its operation. In this contribution we introduce a procedure for the conceptual design of an advanced condition monitoring based on the system's principle solution. The principle solution describes the principal operation mode of the system and its desired behavior. It is modeled using the specification technique for the domain-spanning description of the principle solution of a self-optimizing system and consists of a coherent system of eight partial models (e.g. requirements, active structure, system of objectives, behavior, etc.). The partial models are analyzed separately in order to derive the components of the multi-level dependability concept. In particular, the reliability analysis of the partial model active structure is performed to identify the system elements to be monitored and parameters to be measured. The principle solution is extended accordingly: e.g. with system elements required for the realization of the dependability concept. The advantages of the method are shown on the self-optimizing guidance module of a railroad vehicle.
Keywords: Mechatronic Systems; Principle Solution; Condition Monitoring; Conceptual Design

Analysis of different operation modes for inertia motors - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (ACTUATOR 2012 Conference Proceedings)
Piezoelectric inertia motors, also known as ``stick-slip-drives'', use the inertia of a body to drive it by means of a friction contact in small steps. While these steps normally involve stiction and sliding, the motors can also operate in ``slip-slip'' mode without any phase of static friction. In this contribution, a one degree of freedom model of an inertia motor driven by an ideal actuator is analysed. Start-up and constant velocity operation of the motor are investigated and appropriate quantities to compare ``stick-slip'' and ``slip-slip'' operation are determined. Different aspects such as velocity, uniformity of motion, load capacity, robustness, efficiency, and wear are considered. The analysis allows both modes to be applied advantageously in different applications and can widen the field of application of piezoelectric inertia motors. Motor designers are enabled to choose the appropriate mode of operation and the best drive parameters for their individual applications.
Keywords: Piezoelectric Inertia Motors; Drive Signals; Stick-slip; Slip-slip

Biomimetic approaches to create anti-reflection glass surfaces for solar cells using self-organizing techniques - Achtelik, J.; Sievers, W.; Lindner, Jörg (Materials Science and Engineering: B)
Aiming to diminish the reflection losses of glass covered light harvesting devices, the optical reflectivity of nanostructured glass surfaces is studied theoretically and experimentally. The work is inspired by the nanoscale roughness of insect eyes, which is tried to be replicated on a technical glass surface. To this end, the reflectivity of glass surfaces with topographies represented by linear, parabolic and Fermishaped glass/air fill factor profiles is calculated for normal incidence. It is shown that using the latter ones, an almost complete suppression of reflections can be achieved. A simple, self-organization technique to create such Fermi-shaped filling factor profiles in glass experimentally is also presented.

Growth of cubic GaN on 3C–SiC/Si (001) nanostructures - Kemper, R.M.; Hiller, L.; Stauden, T.; Pezoldt, J.; Duschik, K.; Niendorf, T.; Maier, H.J.; Meertens, D.; Tillmann, K.; As, D.J.; Lindner, Jörg (Journal of Crystal Growth)
We report on the molecular beam epitaxy growth of cubic GaN on 3C–SiC (001) nanostructures. Transmission electron microscopy (TEM) studies show phase-pure cubic GaN crystals with a low defect density on top of the post shaped 3C–SiC nanostructures and GaN grown on their sidewalls, which is dominated by {111} planar defects. The nanostructures, aligned parallel and perpendicular to the [110] directions of the substrate, are located in anti-phase domains of the 3C–SiC/Si (001) substrate. These anti-phase domains strongly influence the optimum growth of GaN layers in these regions. TEM measurements demonstrate a different stacking fault density in the cubic GaN epilayer in these areas.

Self-Organized Nanostructure Formation for Anti-Reflection Glass Surfaces - Achtelik, Jörn; Kemper, Ricarda M.; Sievers, Werner; Lindner, Jörg (MRS Proceedings)
Two methods to create biomimetic anti-reflection nanostructures in ordinary glass microscope object slides are presented. One technique is based on a nanosphere lithography process combined with physical vapour deposition of nickel and reactive ion etching (RIE). The other uses plasma induced dewetting of a smooth nickel surface. The amount of reflected light was measured and a method to simulate the reflectivity from an atomic force microscopy (AFM) topography scan of the glass surface is presented. The reflectivity for visible light at normal incidence was reduced to 20-50 % of the original value with both methods and the simulation gives results in good agreement to the measurement.

Gyrotropic Metamaterials - Brodehl, Christoph; Greulich-Weber, Siegmund; Lindner, Jörg

Formation of defects in cubic GaN grown on nano-patterned 3C-SiC (001) - Kemper, R. M.; Häberlen, M.; Schupp, T.; Weinl, M.; Bürger, M.; Ruth, M.; Meier, Cedrik; Niendorf, T.; Maier, H. J.; Lischka, K.; As, D. J.; Lindner, Jörg (physica status solidi (c))
We report an anisotropic formation of defects in cubic GaN grown on nano-patterned 3C-SiC/Si (001) by molecular beam epitaxy. Nano-patterning of 3C-SiC/Si (001) is achieved by nanosphere lithography and a reactive ion etching process. Atomic force microscopy and scanning electron microscopy show that the selectivearea- grown cubic GaN nucleates in two structurally different domains, which most probably originate from the substrate. In adjacent domains the formation of defects, especially hexagonal inclusions, is different and leads to two different surface morphologies. The dominant phase within these domains was measured by electron backscatter diffraction. Optical properties were investigated by micro-photoluminescence and cathodoluminescence spectroscopy.

TEM investigation of GaN thin films grown on nanostructured 3C-SiC/Si(001) substrates - Kemper, R.M.; Hiller, L.; Stauden, T.; Pezoldt, J.; Meertens, D.; Luysberg, M.; Tillmann, K.; Riedl, Thomas; As, Donald; Lindner, Jörg

Nanosphere Lithography: State-of-the-art and Future Directions - Lindner, Jörg

TEM Characterization of Nickel Nanodot Arrays on Silicon formed by Nanosphere Lithography - Pauly, Johannes; Lindner, Jörg

Nanokugellithographie: Grundlagen und Anwendungen - Lindner, Jörg

Nanolithographie von Oberflächen für das Wachstum optoelektronischer Strukturen - Lindner, Jörg

Dual-polarity plasmonic metalens for visible light - Chen, Xianzhong; Huang, Lingling; Mühlenbernd, Holger; Li, Guixin; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Qiu, Cheng-Wei; Zhang, Shuang; Zentgraf, Thomas (Nature Communications)

Optical properties of cubic GaN from 1 to 20 eV - Feneberg, Martin; Röppischer, Marcus; Cobet, Christoph; Esser, Norbert; Schörmann, Jörg; Schupp, Thorsten; As, Donat Josef; Hörich, Florian; Bläsing, Jürgen; Krost, Alois; Goldhahn, Rüdiger (Physical Review B)

Vibrational fingerprints of LiNbO3-LiTaO3 mixed crystals - Sanna, Simone; Riefer, Arthur; Neufeld, Sergej; Schmidt, Wolf Gero; Berth, Gerhard; Widhalm, Alex; Zrenner, Artur (Proceedings of ISAF-ECAPD-PFM 2012)
The structural and vibrational properties of lithium niobate (LN) – lithium tantalate (LT) mixed crystals (LNT, LiNb1-xTaxO3) are investigated over the whole composition range by first-principles simulations. The crystal volume grows roughly linearly from LT to LN, whereby the lattice parameters a and c show minor deviations from the Vegard behavior between the end compounds, LiNbO3 and LiTaO3. Our calculations in the framework of the density functional theory show the TO1, TO2 and TO4-modes to become harder with increasing Nb concentration. TO3 becomes softer with increasing Nb content, instead. The frequency shifts of the zone center A1-TO phonon modes for crystals with different compositions are found to be as large as 30 cm-1. Raman spectroscopy, which is sensitive to the A1 modes, can be therefore employed to determine the crystal composition.
Keywords: Ferroelectrics; Vibrational properties; LiNbO3; LiTaO3; Mixed Crystals

Coherent optoelectronics with quantum dots - Michaelis de Vasconcellos, Steffen; Gordon, Simon; Mantei, Dirk; Leier, Yves Alexander; Al-Hmoud, M.; Quiring, Wadim; Zrenner, Artur (QUANTUM OPTICS WITH SEMICONDUCTOR NANOSTRUCTURES)
Coherent physics and applications of exciton qubits in electric fi eld tunable quantum dot structures are our focus. Excitations with picosecond (ps) laser pulses result in qubit rotations. Using state projection by tunnelling the readout can be performed in quantitative way. As a function of electric fi eld induced detuning Ramsey fringes of a single exciton qubit can be observed and controlled for double pulse excitation. Therefore it is possible to demonstrate voltage controlled qubit manipulations within a wide range of pulse delays. Using fast electric signals, phase-locked to ps-laser pulses, the coherent control of an exciton qubit can be obtained by electric interaction. Such voltage controlled qubit manipulations seem to be essential for new types of optoelectronic quantum gates and novel applications in the fi eld of coherent optoelectronics.
Keywords: excitons; quantum bits; coherent manipulation; Ramsey interference; quantum gate

A Method for Selectively Designing Modeling Languages for Product-Service Systems - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf (Modeling for Decision Support in Network-Based Services: The Application of Quantitative Modeling to Service Science)

Ansätze zur methodischen Unterstützung der Konstruktion von Produktivitätsmodellen für die Data Envelopment Analysis --- Entwicklung eines Softwareprototypen zur Umsetzung und Evaluation - Becker, Jörg; Knackstedt, Ralf; Beverungen, Daniel; Dietrich, Hanns-Alexander; Breuker, Dominic; Peter Rauer, Hans (Service Engineering --- Management)

Product-Service System Approaches - Beverungen, Daniel; Matzner, Martin; Müller, Oliver; Becker, Jörg (Handbook of Service Description)

Besteuerung von Beteiligungsinvestitionen und Risikoempfindlichkeit – Wie wirkt die Abgeltungssteuer? - Hegemann, Annika

Asymmetric Taxation of Profits and Losses and Its Influence on Investment Timing: Paradoxical Effects of Tax Increases - Mehrmann, Annika; Schneider, Georg; Sureth-Sloane, Caren

Mehr Theorie wagen. Betriebswirtschaftslehre nach Bologna oder Hochschulbildung im Wandel - Sloane, Peter F. E.; Sureth-Sloane, Caren (Wirtschaft und Beruf)

Analytisch und strukturiert denken lernen - Sureth-Sloane, Caren (Frankfurter Allgemeine Zeitung)

Studium nach Bologna: Theorie oder Praxis – ein Scheinwiderspruch? - Sureth-Sloane, Caren (Frankfurter Allgemeine Zeitung)

Unternehmensführung und interkulturelle Hochschulbildung. Unternehmensführung in Europa - Interkulturelle Fragen - Sureth-Sloane, Caren (Wirtschaft und Beruf)

Vorwort. Geschichte des VHB und der BWL: Rückblick und Einblicke - Sureth-Sloane, Caren (Der Verband der Hochschullehrer für Betriebswirtschaft, Geschichte des VHB und Geschichten zum VHB)

Welcher BWLer ist ein guter Forscher? - Sureth-Sloane, Caren; zu Knyphausen-Aufseß, Dodo (Frankfurter Allgemeine Zeitung)

Die Prinzipal-Agent-Theorie als Erklärungsinstrumentarium von Korruption - Gilroy, Bernard Michael; Kruse, Daniel (WiSt-Wirtschaftswissenschaftliches Studium)

Partially Evaluating Finite-State Runtime Monitors Ahead of Time - Bodden, Eric; Lam, Patrick; Hendren, Laurie (ACM Transactions on Programming Languages and Systems)

To buy or not to buy? The value of contradictory analyst signals - Kanne, Stefan; Klobucnik, Jan; Kreutzmann, Daniel; Sievers, Sönke (Financial Markets and Portfolio Management (VHB-JOURQUAL 3 Ranking C))
We study the predictive ability of individual analyst target price changes for post-event abnormal stock returns within each recommendation category. Although prior studies generally demonstrate the investment value of target prices, we find that target price changes do not cause abnormal returns within each recommendation level. Instead, contradictory analyst signals (e.g., strong buy reiterations with large target price decreases) neutralize each other, whereas confirmatory signals reinforce each other. Further, our analysis reveals that large target price downgrades can be explained by preceding stock price decreases. However, upgrades are not preceded by stock price increases, thereby demonstrating asymmetric analyst behavior when adjusting target prices to stock prices. Our results suggest that investors should treat recommendations with caution when they are issued with large contradictory target price changes. Thus, instead of blindly following a recommendation, investors might put more weight on the change in the corresponding target price and consider transaction costs.
Keywords: Analyst recommendation; Target price; Stock performance; Trading strategy

The Relevance of Biases in Management Forecasts for Failure Prediction in Venture Capital Investments - Mokwa, Christopher Frederik; Sievers, Sönke (SSRN Electronic Journal)
This study shows how venture capital investors can identify potential biases in multi-year management forecasts before an investment decision and derive significantly more accurate failure predictions. By advancing a cross-sectional projection method developed by prior research and using firm-specific information in financial statements and business plans, we derive benchmarks for management revenue forecasts. With these benchmarks, we estimate forecast errors as an a priori measure of biased expectations. Using this measure for our proprietary dataset on venture-backed start-ups in Germany, we find evidence of substantial upward forecast biases. We uncover that firms with large forecast errors fail significantly more often than do less biased entrepreneurs in years following the investment. Overall, our results highlight the implications of excessive optimism and overconfidence in entrepreneurial environments and emphasize the relevance of accounting information and business plans for venture capital investment decisions.
Keywords: Management forecast biases; cross-sectional projection models; venture-backed start-ups; failure prediction; overoptimism; overconfidence

Biases in Management Forecasts of Venture-Backed Start-Ups: Evidence from Internal Due Diligence Documents of VC Investors - Mokwa, Christopher; Sievers, Sönke (SSRN Electronic Journal)
This study provides evidence of significant biases in multi-year management forecasts by analyzing a proprietary dataset on venture-backed start-ups in Germany. We find that revenues and expenses are highly overestimated in each of the investigated one- to five-year-ahead planning periods. Furthermore, entrepreneurs underestimate one-year-ahead profit forecasts but clearly overestimate their profit forecasts for all longer-term forecast horizons. Additional analyses reveal that teams with prior management experience issue even more overestimated forecasts and misrepresent their forward-looking information. In contrast, greater asset verifiability and corporate lead investors are associated with lower levels of forecast errors. All key results hold if bias is either measured by traditionally comparing forecasts to ex-post realizations or by using a cross-sectional projection approach based on historical accounting data developed by prior research.
Keywords: Management forecasts; Forecasting biases; Venture-backed start-ups; Projection methods

Add-On Premiums Increase Price Transparency: More Policy Holders Switch Health Plans - Schmitz, Hendrik; Eibich, P.; Ziebarth, N.R. (DIW Economic Bulletin)

Regionale Unterschiede in der stationären Versorgung: Das ländliche Krankenhaus im Fokus - Schmitz, Hendrik; Augurzky, B.; Beivers, A. (Krankenhaus-Report 2012)

Determinanten des Employer Branding in deutschen Unternehmen: Ein neoinstitutionalistischer Erklärungsansatz. - Baum, M; Gsell, L; Kabst, Rüdiger (Die Betriebswirtschaft (ZfB).)

Die Wirkung von informellen und internetbasierten Rekrutierungskanälen auf den Rekrutierungserfolg: Eine empirische Analyse in kleinen und mittleren Unternehmen. - Baum, M; Kabst, Rüdiger (Zeitschrift für Betriebswirtschaft (ZfB).)

Asset Specificity and Foreign Market Entry Mode Choice of Small and Medium-Sized Enterprises: The Moderating Influence of Knowledge Safeguards and Institutional Safeguards. - Maekelburger, B; Schwens, C; Kabst, Rüdiger (Journal of International Business Studies (JIBS).)

Der Einfluss von Rekrutiererverhaltensweisen auf den Bewerber: Ein mediierter Prozess. - Eberz, L M; Baum, M; Kabst, Rüdiger (Zeitschrift für Personalforschung (ZfP).)

Der Personalverantwortliche als strategischer Partner: Persönliche Einstellung oder subjektive Norm? - Wehner, M C; Kabst, Rüdiger; Meifert, M; Cunz, L M (Zeitschrift für Betriebswirtschaft (ZfB).)

Evaluating Major Human Resource Information Systems Design Characteristics: An Empirical Analysis. - Strohmeier, S; Kabst, Rüdiger (International Journal of Business Information Systems (IJBIS).)

Evidence-based entrepreneurship (EBE): Cumulative science, action principles, and bridging the gap between science and practice. - Frese, M; Bausch, A; Schmidt, P; Rauch, A; Kabst, Rüdiger (Foundations and Trends in Entrepreneurship.)

Graduates’ Reactions to Recruitment Process Outsourcing: A Scenario-Based Study. - Wehner, M C; Giardini, A; Kabst, Rüdiger (Human Resource Management.)

Greenfield Investment versus Akquisition: Der moderierende Einfluss wahrgenommener institutioneller Unsicherheit bei der Internationalisierung von KMU. - Eiche, J; Schwens, C; Kabst, Rüdiger (Zeitschrift für Betriebswirtschaft (ZfB).)

Internationaler Joint Venture Erfolg: Eine Meta-Analyse. - Isidor, R; Schwens, C; Kabst, Rüdiger; Hornung, F (Zeitschrift für Betriebswirtschaft (ZfB).)

Testing the Circular Structure of Human Values: A Meta-Analytical Structural Equation Modelling Approach. - Steinmetz, Holger; Isidor, R; Bäuerle, N (Survey Research Methods)

A Fuzzy Decision Support Model for Natural Disaster Response under Informational Uncertainty - Wex, Felix; Schryen, Guido; Neumann, Dirk (International Journal of Information Systems for Crisis Response and Management)

Operational Emergency Response under Informational Uncertainty: A Fuzzy Optimization Model for Scheduling and Allocating Rescue Units - Wex, Felix; Schryen, Guido; Neumann, Dirk (International Conference on Information Systems for Crisis Response and Management (ISCRAM) 2012)

IS Design Thinking in Disaster Management Research - Schryen, Guido; Wex, Felix (45th Hawaii International Conference on System Sciences)

Profis im Netz: Soziale Netzwerke könnten in Unternehmen viel mehr Nutzen stiften - woran hakt es?, in: Die Zeit (12.04.2012) - Schryen, Guido (Die Zeit)

Soziale Netzwerke in Unternehmenskontexten - Potentiale und Anforderungen, in: Information Management & Consulting, to appear - Schryen, Guido (IM Information Management & Consulting)

Weaving-based configuration and modular transformation of multi-layer systems - Besova, Galina; Walther, Sven; Wehrheim, Heike; Becker, Steffen (Proceedings of the 15th International Conference on Model Driven Engineering Languages & Systems (MoDELS))
In model-driven development of multi-layer systems (e.g. application, platform and infrastructure), each layer is usually described by separate models. When generating analysis models or code, these separate models rst of all need to be linked. Hence, existing model transformations for single layers cannot be simply re-used. In this paper, we present a modular approach to the transformation of multi-layer systems. It employs model weaving to dene the interconnections between models of dierent layers. The weaving models themselves are subject to model transformations: The result of transforming a weaving model constitutes a conguration for the models obtained by transforming single layers, thereby allowing for a re-use of existing model transformations. We exemplify our approach by the generation of analysis models for component-based software.

Untersuchung von Modellen zur operativen Planung in Trinkwasserversorgungsnetzwerken - Hilger, Ina

Berufsorientierung im Übergang - Überlegungen zur curricularen Gestaltung der Bildungsarbeit im Übergangssystem - Kremer, H.-Hugo (Individuelle Förderung und berufliche Orientierung im berufsschulischen Übergangssystem - Ergebnisse aus dem Forschungs- und Entwicklungsprojekt InLab)

Funktionen und Erträge pädagogischer Diagnostik im wirtschafts- und berufspädagogischen Bereich (Editorial) - Tramm, T.; Seeber, S.; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik - online)

Akademisierung der Berufsbildung - Editorial - Büchter, K.; Frommberger, D.; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik - online)

Optimized XPath evaluation for Schema-compressed XML data - Böttcher, Stefan; Hartel, Rita; Heindorf, Stefan (ADC)

Generalized Kripke semantics for the Lambek-Grishin calculus - Chernilovskaya, A.; Gehrke, M.; van Rooijen, Lorijn (Logic Journal of IGPL)

Generalizing and Improving SQL/XML Query Evaluation - Böttcher, Stefan; Bokermann, Dennis; Hartel, Rita (8th International Conference on Signal Image Technology and Internet Based Systems (SITIS'12))

Spatial Representations of British Identities

A Bricolage of Identities in Crisis. Colour Photography Documenting Northern England under Thatcher - Tönnies, Merle (Facteurs d'Identité / Faktoren der Identität)

Measurement of spectral-spatial distribution of global irradiance - Leers, Mathias; Preiss, Alexander; Ferretti, Nicoletta; Krauter, Stefan (2011 37th IEEE Photovoltaic Specialists Conference)

Suitable test procedure for electrical energy storage in PV operation mode – implementation and implication - Krauter, Stefan; Lang, o. (7th International Renewable Energy Storage Conference (IRES 2012), Berlin (Germany), 12.-14. November 2012)

PV 3.0 - Krauter, Stefan (Proceedings of the 27th European Photovoltaic Solar Energy Conference and Exhibition, Frankfurt a. M. (Germany), 24.-28. September 2012, pp. 4520-4522)

Technical Assurance for High Reliable PV Modules via PI Testing - Krauter, Stefan; Chen, S. (Proceedings of 6th International Photovoltaic Power Generation Conference SNEC 2012, Shanghai (China), 16.-18. June 2012)

Solar PV in Latin America. - Krauter, Stefan (PV Magazine April 2012)

Encapsulation influence on the potentialinduced degradation of crystalline silicon cells with selective emitter structures. - Koch, S.; Berghold, J.; Okoroafor, O.; Krauter, Stefan; Grunow, Paul (Proceedings of the 27th European Photovoltaic Solar Energy Conference and Exhibition, Frankfurt a. M. (Germany), 24.-28. September 2012, pp. 1991-1995)